Two tribes - Bowen Cohen, Emily (Heartdrum, HarperAlley, imprints of HarperCollins Publishers, 2023)
"Mia is still getting used to living with her mom and stepfather, and to the new role their Jewish identity plays in their home. Feeling out of place at home and at her Jewish day school, Mia finds herself thinking more and more about her Muscogee father, who lives with his new family in Oklahoma. Her mother doesn't want to talk about him, but Mia can't help but feel like she's missing a part of herself without him in her life. Soon, Mia makes a plan to use the gifts from her bat mitzvah to take a bus to Oklahoma--without telling her mom--to visit her dad and find the connection to her Muscogee side she knows is just as important as her Jewish side"--